Mt. Banahaw reveals: The resurrection and neotypification of the name Rafflesia lagascae (Rafflesiaceae) and clues to the dispersal of Rafflesia seeds - Pelser, Pieter B.; Nickrent, Daniel L.; Callado, John Rey C.; Barcelona, Julie F. (Phytotaxa, 2013)
The southeast Asian holoparasite genus Rafflesia Brown (1821: 207; Rafflesiaceae) is famous for producing the largest flowers on record (Kuijt 1969). Following a series of discoveries of new Rafflesia species and populations, the Philippines recently emerged as one of the centers of its diversity. It is home to no less than ten currently recognized Rafflesia species (Barcelona et al. 2009, Balete et al. 2010). Here, we report two discoveries that resulted from recent fieldwork in the Mts. Banahaw - San Cristobal Protected Landscape in Luzon and show how these new data impact the taxonomy and biology of Philippine Rafflesia.